A global proficiency testing programme for Xpert® MTB/RIF using dried tube specimens, 2013-2015 - Katherine Klein; Kyle DeGruy; Zilma Rey; Patricia Hall; Andrea Kim; Steve Gutreuter; Heather Alexander (AOSIS, 2020)
Background: Proficiency testing (PT) is an important quality assurance measure toward ensuring accurate and reliable diagnostic test results from clinical and public health laboratories. Despite the rapid expansion of the Xpert® MTB/RIF assay for the detection of tuberculosis in resource-limited settings (RLS), low-cost PT materials for Xpert MTB/RIF external quality assessment (EQA) are not widely available. Objective: We sought to determine whether a dried tube specimen (DTS)-based PT programme would be a feasible option to support Xpert MTB/RIF EQA in RLS. Methods: Between 2013 and 2015, the United States Centers for Disease Control and Prevention developed and conducted a voluntary EQA programme using DTS-based PT material. Eight rounds of PT, each comprising five DTS samples, were provided to enrolled testing sites. After each round, participant results were compared to expected results, scored as satisfactory or unsatisfactory, and sites were provided with performance reports. Results: Programme enrolment increased from 102 testing sites in seven countries to 441 testing sites in 14 countries over the course of three years. In each PT round, approximately 90% of participating sites demonstrated satisfactory performance. In seven of the 14 enrolled countries, the proportion of sites with a satisfactory score increased between the first round of participation and the most recent round of participation. Conclusion: This programme demonstrated that it is possible to implement an Xpert MTB/RIF PT programme for RLS using DTS, that substantial demand for Xpert MTB/RIF PT material exists in RLS, and that country performance can improve in a DTS-based PT programme.